Review of Sharia Economic Law: Determination of Murabahah Financing Margins at Kospin Jasa Syariah Kendal - Savella Ajeng Kusumawardhani; Akhmad Nurasikin; Ubbadul Adzkiya’ (International Journal of Law, 2025)
Kospin Jasa Syariah is one of the Islamic financial institutions that operates in accordance with sharia principles. However, one of the policies set, namely the determination of the amount of profit margin determined from the start with the flat rate method, is in accordance with sharia rules. The objectives of this study are (1) To determine the determination of profit margins in murabahah financing at Kospin Jasa Syariah Kendal. (2) To know the view of sharia economic law on the determination of profit margin in murabaha financing. The research method used is qualitative. This research is included in the type of field research (field research) with a qualitative research approach and data collection with interview techniques, documentation and direct observation.The results of this study are Determination of the profit margin for murabaha financing at Kospin Jasa Syariah Kendal with the provisions of profit margins such as determining the category of financing under 25 million with a margin of 15%, between 25 million and 250 million with a margin of 11.52%, 250 million and above with a margin of 10.72%, based on mutual agreement between both parties between Kospin and customers. The view of sharia economic law on the practice of determining profit margins in murabaha financing is permissible. This is in accordance with the DSN MUI fatwa NO 04/DSN-MUI/IV/2000, the Compilation of Sharia Economic Law and the regulations of Law No. 21 of 2008 Article 19 paragraph (1) concerning Islamic Banking.